A Typology of Plants in Global Manufacturing Networks - Vereecke, Ann (Institutional Knowledge at Singapore Management University, 2006)
The purpose of this paper is to propose a new, empirically derived typology of plants in the international manufacturing network of multinational companies. This typology is based on the knowledge flows between the plants. In our research, network analysis has been used as a methodology for understanding the position of plants in international manufacturing networks. The focus has been primarily on the intangible knowledge network, and secondarily on the physical, logistic network. Our analysis leads to four types of plants with different network roles: the isolated plants, the receivers, the hosting network players, and the active network players. Our analysis shows that the different types of plants play a different strategic role in the company, have a different focus, and differ in age, autonomy, and level of resources and investments. Also, the analysis suggests that the evolution of the plant depends to some extent on the network role of the plant. Finally, two scenarios for the development of a strong network role are identified. The research is useful for the scholar studying the architecture of knowledge networks, as well as for the practitioner who is in charge of an international network of manufacturing units.